2023
DOI: 10.1002/14651858.cd015078
|View full text |Cite
|
Sign up to set email alerts
|

Antiplatelet agents for the treatment of adults with COVID-19

Abstract: BackgroundSevere coronavirus disease 2019 (COVID-19) can cause thrombotic events that lead to severe complications or death. Antiplatelet agents, such as acetylsalicylic acid, have been shown to e ectively reduce thrombotic events in other diseases: they could influence the course of COVID-19 in general. ObjectivesTo assess the e icacy and safety of antiplatelets given with standard care compared to no treatment or standard care (with/without placebo) for adults with COVID-19. Search methodsWe searched the Coc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 64 publications
1
4
0
Order By: Relevance
“…We found a two-fold higher risk for major bleeding in patients undergoing AP treatment at the time of hospitalization in the univariate analysis [HR 2.65 (95%CI 1.27-5.52)], but we did not confirm this data in the multivariate analysis, although there was the non-significant estimated two-fold higher risk [AHR 1.98 (95% CI 0.92-4.30)] when compared to individuals not exposed to AP at the time of hospital admission. This finding is in accordance with what is reported in the literature, both for critically ill [47] and not critically ill patients with COVID-19 infection [48], and, also, in patients not hospitalized for COVID-19 disease [42,49]. It is known that the AP effect of the more common AP drugs have a time-to-platelet function recovery after drug interruption of about 5-7 days [50], making the summatory effect on bleeding risk of AC therapy and chronic AP therapy at admission nearly inevitable.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found a two-fold higher risk for major bleeding in patients undergoing AP treatment at the time of hospitalization in the univariate analysis [HR 2.65 (95%CI 1.27-5.52)], but we did not confirm this data in the multivariate analysis, although there was the non-significant estimated two-fold higher risk [AHR 1.98 (95% CI 0.92-4.30)] when compared to individuals not exposed to AP at the time of hospital admission. This finding is in accordance with what is reported in the literature, both for critically ill [47] and not critically ill patients with COVID-19 infection [48], and, also, in patients not hospitalized for COVID-19 disease [42,49]. It is known that the AP effect of the more common AP drugs have a time-to-platelet function recovery after drug interruption of about 5-7 days [50], making the summatory effect on bleeding risk of AC therapy and chronic AP therapy at admission nearly inevitable.…”
Section: Discussionsupporting
confidence: 93%
“…We found that length of stay (median days) was significantly longer in patients with a major bleeding event [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] vs. 14 (IQR 8-24), p < 0.0001)] (Table 3). Death was more frequently observed in patients with major bleeding (34.5% vs. 18.0%, p = 0.039).…”
Section: Outcome Of Subjects With a Major Bleeding Eventmentioning
confidence: 92%
“…Anticoagulation has been shown to be more effective in preventing thromboembolic events in atrial brillation which may also explain the lower number of ischemic strokes and TIA in the non-AP group. AP treatment is a well-known risk factor for major bleeding, especially in long-term observation, in older patients, and without the routine use of proton-pump inhibitors (PPI) [37][38][39]. We did not nd any signi cant differences between the groups in terms of hemorrhagic complications.…”
Section: Ap -Antiplatelet Treatmentmentioning
confidence: 83%
“…It should be emphasized that patients with severe disease at baseline (requiring intensive care support) were not included in the study, which contrasts with our analysis in which we examined the entire spectrum of COVID-19 patients requiring hospitalization. Likely, this group of patients would bene t more from AP treatment as it may reduce the increased in ammatory response that underlies the complications of COVID-19, such as septic processes and acute lung injury [39].…”
Section: Ap -Antiplatelet Treatmentmentioning
confidence: 99%
“…Current data do not support the use of antiplatelet agents, including aspirin or P2Y12 inhibitor, ticagrelor for either outpatients or inpatients with COVID-19. Systematic review and meta-analysis of four RCTs, including 17,541 hospitalized patients with moderate to severe COVID-19, revealed that antiplatelets had no effect on 28-day mortality and clinical improvement but probably resulted in a slight reduction in thrombotic events and an increase of major bleeding events ( 130 ). Recent RCTs also do not support using antiplatelets to treat COVID-19 ( 131 ).…”
Section: Antiplatelet Therapymentioning
confidence: 99%